2021
DOI: 10.3389/fpsyt.2021.653245
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Suicidal Ideation With Family Characteristics and Social Support of the First Batch of Students Returning to a College During the COVID-19 Epidemic Period: A Cross Sectional Study in China

Abstract: Objective: To investigate the prevalence of suicidal ideation among the first batch of students returning to a college during the COVID-19 epidemic, and to explore the correlation of suicidal ideation with family characteristics and social support.Methods: A cluster sampling survey with a self-designed questionnaire was conducted among the first batch of students returning to a college in Wuhu, China. The Positive and Negative Suicidal ideation (PANSI) and Social Support Scale (SSRS) were used to define studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
3
9
1
Order By: Relevance
“…Furthermore, we found different effects of sex on the cumulative risk model. Males reported a higher rate of SIs than females during the COVID-19 pandemic, which is in agreement with previous studies ( Chen et al, 2021 ; Zhou et al, 2021 ). In addition, relative to females, males with more than two mental risks were susceptible to sharply increased SIs during the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we found different effects of sex on the cumulative risk model. Males reported a higher rate of SIs than females during the COVID-19 pandemic, which is in agreement with previous studies ( Chen et al, 2021 ; Zhou et al, 2021 ). In addition, relative to females, males with more than two mental risks were susceptible to sharply increased SIs during the COVID-19 outbreak.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, significant sex differences in SIs have been reported ( Chen et al, 2021 ; Zhou et al, 2021 ; Zhu et al, 2022 ). The prevalence of SIs in females (3.6%) was higher than the prevalence of SIs in males (2.4%) during the COVID-19 pandemic ( Zhu et al, 2022 ), while another study suggested that the prevalence of SIs in males (7.9%) was higher than the prevalence of SIs in females [4.6%] ( Chen et al, 2021 ). In addition, distinct risk factors for SIs were also confirmed in previous studies ( Chen et al, 2021 ; Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pre-existing bipolar disorders, facilitated by isolation or loss of reference points caused by the reduction of community care activities, may have manifested imbalances and increased suicidal ideation ( Gunnell et al, 2020 ; Vindegaard and Benros, 2020 ). The occurrence of self-injurious urges may also have occurred in previously unknown patients due mainly to the side effects of the pandemic on work and family status ( Chen et al, 2021 ; Gunnell et al, 2020 ). As previous research after other human catastrophes has shown, job loss and the inability to plan for the future can cause non-negligible long-term effects on mental health and could explain the increasing trends observed in our study ( Holland et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, men had an increased perception of loneliness compared to women during the COVID-19 pandemic lockdown compared to before it [ 42 ]. Moreover, there are some studies which showed that rates of suicidal ideation in men were higher than in women [ 43 , 44 , 45 ]. These findings might support the results of this study.…”
Section: Discussionmentioning
confidence: 99%